Artificial intelligence and responsible management education : current applications and future directions - El-Bassiouny, Noha; Amann, Wolfgang; El-Bassiouny, Dina; Hauser, Christian (Routledge, 2026)
Artificial Intelligence and Responsible Management EducationArtificial Intelligence (AI) offers considerable opportunities, as well as challenges, to management education and research. This book brings together case studies and best practice examples of the use of AI in advancing diverse fields relating to Responsible Management Education (RME).Moving beyond the conceptual questions about the use of AI in management education, the book identifies the real-world application of AI and showcases exemplary policies related to AI and its role in advancing responsible management in higher education institutions. Interesting cases include the development of curricula, AI-powered personalized learning, the implications of using AI in short-answer grading, and the utilization of AI in auditing and investment.The book is relevant to educators and scholars worldwide, as well as managers of universities and business schools as they navigate what it entails to advance responsible management education in the AI era.
Keywords: Artificial intelligence -- Educational applications.; Management education; AI; Artificial intelligence; Responsible business; PRME; Principles of Responsible Management Education; Innovation management; Business schools; Business curricula; elektronické knihy; electronic books